Profile of hemodialysis patients in the Brusque Region, State of Santa Catarina (SC), Brazil (Research, Society and Development, 2024)
Introduction: Chronic Kidney Disease (CKD) is a multifactorial pathology. Depending on its severity, treatment consists of dialysis, with hemodialysis being the most used method in Brazil. The objective of this study was to develop a profile of hemodialysis patients in the region of Brusque, Santa Catarina, Brazil, addressing aspects of general, socioeconomic data, treatments, lifestyle, quality of life, level of satisfaction with the service, and an approach to spirituality. Method: This study is descriptive, cross-sectional, with a qualitative and quantitative approach, carried out at the Hemodialysis Center in the Brusque region. Data collection was conducted using a structured questionnaire, divided into six blocks based on the guidelines of Toassi & Petry (2021). The data were tabulated and organized in Microsoft Excel 2019 software, through simple descriptive analysis, following the recommendations of the aforementioned authors. Results: Encompassing 75%, it revealed a diverse patient profile. In summary, the majority of participants were between 51 and 72 years old, predominantly residents of Brusque, male, married, with low education, who consider themselves religious and have a monthly income of up to 2,000 reais. Regarding the evaluation of the service, the results were positive, with emphasis on the good relationship between patients and doctors and nurses. Regarding religious beliefs, the results show that this plays a significant role in the patient's life and is a source of emotional support. Conclusions: Understanding this diverse profile is essential to improve quality of life, adherence, and clinical results of treatment